The Banathy Model: An Innovation to Improve the Quality of Inquiry Learning - Neneng Nurlaela; Eva Dianawati Wasliman; Kokom Komalasari (MASI Mandiri Edukasi, 2026)
Although inquiry learning is widely recognized as an effective approach to promote critical thinking and active student engagement, its classroom implementation often remains procedural and less systematic, resulting in suboptimal learning quality. The Banathy Model, as a systems-based instructional design approach, offers a structured framework to strengthen inquiry learning processes. This study aims to analyze the implementation of the Banathy Model as an innovation to improve the quality of inquiry learning in junior high school. This research employed a qualitative approach with a descriptive case study design conducted at Sekolah Menengah Pertama 1 Arjasari, Bandung Regency. The participants consisted of five teachers and twenty seventh-grade students. Data were collected through in-depth interviews, classroom observations, and documentation studies, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the implementation of the Banathy Model enhances the quality of inquiry learning by promoting structured lesson planning, systematic learning stages, and active student participation. Students demonstrated increased engagement in group discussions, improved questioning skills, and greater involvement in problem-solving activities. The model also supported teachers in organizing inquiry-based instruction more effectively. The study contributes theoretically to the development of systems-based instructional design in inquiry learning and practically provides guidance for teachers and schools in implementing innovative learning models to improve classroom learning quality.